2020
DOI: 10.26508/lsa.202000934
|View full text |Cite
|
Sign up to set email alerts
|

Paneth cell–derived growth factors support tumorigenesis in the small intestine

Abstract: Paneth cells (PCs) are small intestinal epithelial cells that secrete antimicrobial peptides and growth factors, such as Wnt ligands. Intriguingly, the context in which PC-derived Wnt secretion is relevant in vivo remains unknown as intestinal epithelial ablation of Wnt does not affect homeostatic proliferation or restitution after irradiation injury. Considering the importance of growth factors in tumor development, we explored here the role of PCs in intestinal carcinogenesis using a genetic model of PC depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
(55 reference statements)
1
5
0
Order By: Relevance
“…It has been reported that Paneth cell-specific deletion of Wnt3 leads to a reduction in small intestinal tumors but not colonic tumors in Apc Min/? mice [43]. We speculated that Wnt3 production might be reduced in the LAT1 fl/fl ; vilcre small intestine, and as expected, Wnt3 expression was substantially reduced at both the mRNA and protein levels (Fig.…”
Section: Organoids Derived From Lat1-deleted Tumors Displayed Fewer A...supporting
confidence: 58%
See 1 more Smart Citation
“…It has been reported that Paneth cell-specific deletion of Wnt3 leads to a reduction in small intestinal tumors but not colonic tumors in Apc Min/? mice [43]. We speculated that Wnt3 production might be reduced in the LAT1 fl/fl ; vilcre small intestine, and as expected, Wnt3 expression was substantially reduced at both the mRNA and protein levels (Fig.…”
Section: Organoids Derived From Lat1-deleted Tumors Displayed Fewer A...supporting
confidence: 58%
“…It would be acceptable to explain that the tumor number was not affected because the colon lacks Paneth cells; our data is further supported by a previous report, which showed Paneth cellspecific deletion of Wnt3 blocked Apc Min/? tumor formation in the small intestine but not in the colon [43]. Even so, LAT1 deficiency could have influenced tumor size.…”
Section: Discussionmentioning
confidence: 98%
“…Chen et al [ 109 ] showed cells of the Paneth cell lineage are present in intestinal adenomas. They secrete Wnt 3 and a deletion of Paneth cells leads to reduced growth of adenomas in the small intestine in APC min mice.…”
Section: Clinical Relevance Of Wnt Activation In the Intestinementioning
confidence: 99%
“…Apart from being the source of stem cell signals in the small intestine, Paneth cells have previously been associated with β-catenin pathway activation in human adenomas [ 23 ] and a specific Paneth cell population expressing indoleamine-2,3-dioxygenase-1 was found to promote immune evasion in human colorectal cancer [ 24 ]. However, it remains controversial whether and how the presence of Paneth cells positively or negatively impact CRC malignancy [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%